2021
DOI: 10.1016/j.pedn.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Women's Empowerment and Determinants of Early Initiation of Breastfeeding: A Scoping Review

Abstract: Introduction: Early initiation of breastfeeding (EIBF), the immediate provision of mothers' breast milk to infants within the first hour of life, has been recommended by the WHO. However, EIBF is not widely practiced, thereby increasing infant mortality risk. This review explored the available and published studies that identified interventions that empower mothers to practice EIBF. Method: We conducted a scoping review to answer the aforementioned aims. Empowerment, Women, Breastfeed, and Initiation were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 52 publications
(174 reference statements)
2
26
0
1
Order By: Relevance
“…Consistent with previous studies, the current study reported a statistically significant positive association between EIBF and older maternal age,23 multiparity,23 24 female infant,25 rural residence,23 wealthier household,23–25 health facility delivery,17 23 mothers not working within the last 12 months and mother on leave for the last 7 days 26. Similarly, in congruence with previous studies, this study found a statistically significant negative association between EIBF and caesarean delivery,14 17 18 23–25 small-sized infant during birth23 24 and mother in marital union 26.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies, the current study reported a statistically significant positive association between EIBF and older maternal age,23 multiparity,23 24 female infant,25 rural residence,23 wealthier household,23–25 health facility delivery,17 23 mothers not working within the last 12 months and mother on leave for the last 7 days 26. Similarly, in congruence with previous studies, this study found a statistically significant negative association between EIBF and caesarean delivery,14 17 18 23–25 small-sized infant during birth23 24 and mother in marital union 26.…”
Section: Discussionsupporting
confidence: 91%
“…Nigeria [18], Namibia [39], West Africa state [23], Nepal [40,41], India [26], Indonesia [8, 27,42], Bangladesh [43,44], South Asia [45], Middle East [28], Turkey [46], Romania [47]. A secondary analysis of the WHO Global survey published in 2017 also showed EIBF to be signi cantly lower among women with caesarean section delivery [22].…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian yang dilakukan oleh Adewuyi et al (2017) bahwa keberhasilan IMD di daerah perkotaan lebih tinggi daripada daerah pedesaan. Penelitian lain secara scoping review ditemukan bahwa faktor-faktor penghambat IMD adalah operasi caesar, nyeri paska persalinan, masalah laktasi dan komplikasi kehamilan, faktor sosial dan demografi, rendahnya dukungan ibu, kondisi bayi, sedangkan yang menunjang IMD adalah perilaku positif ibu terkait tingkat pendidikan, perawatan antenatal yang lengkap, ekonomi ibu, dan ukuran bayi (Hadisuyatmana et al, 2021).…”
Section: Pendahuluanunclassified